Thyroid disease following the administration of Thorotrast - Langlands, A. O. (1967)
Four cases of thyrotoxicosis are reported among 35 patients who had been given Thorotrast during the investigation of intracranial haemorrhage. For the group as a whole Thorotrast had been given between 11 and 31 years (mean 23·4 years) before this study. Thyrotoxicosis occurred in four patients between six and 17 years (mean 11·8 years) after the injection of Thorotrast. The fact that thyrotoxicosis did not occur in a small control group of patients who had had a subarachnoid haemorrhage and in whom Thorotrast had not been used at angiography suggests that Thorotrast may be of aetiological significance. In view of the known association between thyrotoxicosis and changes in the lymphoreticular system it is possible that the irradiation of this system by retained thorium has resulted in an abnormality of function which renders these patients more liable to the development of thyrotoxicosis. A fifth patient developed non-toxic thyroid enlargement 16 years after Thorotrast angiography.